Urgensi Literasi Digital dalam Meningkatkan Keterampilan Abad 21 di Sekolah Dasar: Kajian Literatur dan Strategi Implementasi - Nur Fatmawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The transformation of digital technology demands the strengthening of digital literacy since the primary education level. This study aims to examine the urgency of digital literacy in shaping 21st century skills and formulate contextual implementation strategies. This research uses a literature study approach by analyzing five national and international scientific articles relevant to the topic of digital literacy in primary education, published between 2019-2025. The data analysis technique used was thematic content analysis, by systematically reviewing the contents of ten national and international scientific articles to identify the main themes related to the urgency of digital literacy and its implementation strategies in basic education. The results of the literature review of the last ten national and international articles show that digital literacy plays an important role in developing students' critical thinking, collaboration, communication and creativity skills. However, challenges such as disparities in access to technology and lack of teacher training remain significant barriers. Therefore, a collaborative strategy between teachers, schools and government is needed to strengthen digital literacy in primary schools.Transformasi teknologi digital menuntut penguatan literasi digital sejak jenjang pendidikan dasar. Kajian ini bertujuan untuk mengkaji urgensi literasi digital dalam membentuk keterampilan abad ke-21 serta merumuskan strategi implementasi yang kontekstual. Penelitian ini menggunakan pendekatan studi literatur dengan menganalisis lima artikel ilmiah nasional dan internasional yang relevan dengan topik literasi digital di pendidikan dasar, terbit antara 2019–2025. Teknik analisis data yang digunakan adalah analisis konten tematik, dengan menelaah isi dari sepuluh artikel ilmiah nasional dan internasional secara sistematis untuk mengidentifikasi tema-tema utama terkait urgensi literasi digital dan strategi implementasinya di pendidikan dasar. Hasil kajian pustaka terhadap artikel nasional dan internasional sepuluh lima terakhir menunjukkan bahwa literasi digital berperan penting dalam mengembangkan kemampuan berpikir kritis, kolaborasi, komunikasi, dan kreativitas siswa. Namun demikian, tantangan seperti kesenjangan akses teknologi dan minimnya pelatihan guru masih menjadi hambatan signifikan. Oleh karena itu, diperlukan strategi kolaboratif antara guru, sekolah, dan pemerintah untuk memperkuat literasi digital di sekolah dasar.